Testing parent dyad interchangeability in the parent proxy-report of PedsQL™ 4.0: a differential item functioning analysis. - Doostfatemeh, Marziyeh; Ayatollahi, Seyyed Mohammad Taghi; Jafari, Peyman (Quality of Life Research, 2015)
Purpose: In child-parent agreement studies in the field of paediatric health-related quality of life (HRQoL), little attention has been paid to the effect of gender in parental proxy rating of children's HRQoL. This study aims to test the potential interchangeability of parent dyads in reporting children's HRQoL on both item and scale levels of the PedsQL™ 4.0 instrument, using the approach of differential item functioning (DIF).Methods: The PedsQL™ 4.0 Generic Core Scales were completed by 576 father-and-mother dyads. A polytomous item response theory model, graded response model, was used to detect DIF across fathers and mothers.Result: Assessment at item level showed that fathers and mothers perceived the meaning of items of the PedsQL™ 4.0 consistently. Regarding the scale level, a moderate to high level of agreement was observed between mothers' and fathers' reports on all similar subscales. Although the significant mean score differences in total, physical and emotional functioning indicated that fathers gave higher scores to their children, the small effect size implied that this difference may not be practically meaningful.Conclusion: Our findings revealed that discrepancy in parent dyads in rating children's HRQoL is a "real" difference and not an artefact due to measurement non-invariance. Fathers were seen to have slightly different insights into their children, especially for emotional functioning, but overall the results were not all that different. This suggests that paternal proxy-reports can be included in studies along with maternal proxy-reports, and the two may be combined when looking at parent-child agreement. Parent-child agreement studies in Iran are not affected by parents' gender, and therefore, researchers may rely on the assumption of the interchangeability of fathers and mothers in these studies.